Efektivitas Kanamycin terhadap Furunculosis pada Karper, Cyprinus carpio - Sri Retnoningsih; Kamiso H. Nitimulyo; Kardiman Lanadimulya; Suprayogi Suprayogi; Supardi Supardi; Djoko Darmantani; I P. Panca; Hasnah Hasnah; Soefaad Soefaad; Milis Milis (Jurnal Perikanan Universitas Gadjah Mada, 2009)
The aim of experiment was to know the appropriate and effective dosis of kanamycin antibiotic in order to recover and clean the Aeromonas salmonicida which caused furunculosis in carp, Cyprinus carpio. The experiment consisted of the preliminary test [revirulence of A. salmonicida, sensitivity, minimum inhibitory concentration (MIC), minimum bactericidal concentration test (MBC), lethal concentration-50 (LC50) of A. salmonicida to carp] and the effectiveness antibiotic kanamycin test. The water quality was analyzed at the beginning and the end of the experiment, histopathology was analyzed at the end of the experiment. The data were analyzed using analysis of variance (ANOVA) continued by least significant different and regression tests.Based on the result of in vitro test, it was obtained that the value of MIC was 4 ppm and the value of MBC was 8 ppm, while the result of lethal concentration-50 (LC50) A. salmonicida to carp was 1.07 x 105  cell/ml. Survival rate of carp at the end of experiment were 20% (treatment 0 ppm); 73,3% (treatment 16 ppm); 86.7% (treatment 32 ppm); 93.3% (treatment 48 ppm); 96.7% (treatment 64 ppm); and 100% (treatment 80 ppm). The survival rates were very significance difference (P <0,01) among treatments and the treatments of kanamycin were very significant difference (P <0.01) from positif control. The regression showed that there was correlation between the concentration of kanamycin and survival rates of carp by coefficient of correlation (R2) at 0.9382.